Genomic organization and dynamics of repetitive DNA sequences in representatives of three Fagaceae genera - Alves, Sofia; Ribeiro, Teresa; Inácio, Vera; Rocheta, Margarida; Morais-Cecílio, Leonor (Genome, 2012)
Oaks, chestnuts, and beeches are economically important species of the Fagaceae. To understand the relationship between these members of this family, a deep knowledge of their genome composition and organization is needed. In this work, we have isolated and characterized several AFLP fragments obtained from Quercus rotundifolia Lam. through homology searches in available databases. Genomic polymorphisms involving some of these sequences were evaluated in two species of Quercus, one of Castanea, and one of Fagus with specific primers. Comparative FISH analysis with generated sequences was performed in interphase nuclei of the four species, and the co-immunolocalization of 5-methylcytosine was also studied. Some of the sequences isolated proved to be genus-specific, while others were present in all the genera. Retroelements, either gypsy-like of the Tat/Athila clade or copia-like, are well represented, and most are dispersed in euchromatic regions of these species with no DNA methylation associated, pointing to an interspersed arrangement of these retroelements with potential gene-rich regions. A particular gypsy-sequence is dispersed in oaks and chestnut nuclei, but its confinement to chromocenters in beech evidences genome restructuring events during evolution of Fagaceae. Several sequences generated in this study proved to be good tools to comparatively study Fagaceae genome organization.
doi: 10.1139/g2012-020doi: 10.1139/g2012-020The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: AFLP; Castanea; euchromatin; Fagaceae; Fagus; Quercus; retroelements